بإضافة تراكيز من حامض الساليسليك خارج الجسم الحي. graecum- foenum Trigonella .L تحفيز إنتاج بعض مركبات األيض الثانوي في كالس نبات الحلبة - عباس استبرق سامي; محمود سعدية حسن; إبراهيم كاظم محمد (Al-Nahrain Journal of Science, 2018)
The effect of adding different concentrations of salicylic acid (0, 50, 100, 150 or 200 mg/l) on the production of some secondary metabolites in callus of Trigonella foenum- graecum L. plant was studied. The quality and quantity of phytochemicals were investigated using methanol extracts of hypocotyls seedlings in vivo, in vitro. Calli were analyzed using high performance liquid chromatography (HPLC). Callus was initiated on dissected hypocotyls explants using Murashige and Skoog (1962) (MS) medium supplemented with Benzyl adenine (BA) at 1.5 mg/l with 0.5 2